Fenomena Korupsi Berulang di Indonesia: Apakah Pendidikan Anti Korupsi Gagal? - Kania Azzahra; Qeysa Amruny Nasution (Polyscopia, 2026)
Corruption in Indonesia continues to demonstrate persistent and increasingly complex recurrence despite the implementation of various preventive strategies, positioning Anti-Corruption Education as a central instrument for long-term character formation. This study investigates the underlying factors contributing to the persistence of corrupt practices and evaluates the effectiveness of Anti-Corruption Education in achieving its normative objectives. A qualitative descriptive approach was employed through a systematic literature review of scholarly sources published between 2017 and 2025. The findings indicate that Anti-Corruption Education cannot be categorically deemed ineffective; however, its impact remains constrained by structural weaknesses, cultural normalization of corruption, and inconsistencies between normative educational values and real-world governance practices. The absence of credible role models among political elites further undermines its transformative potential. The study argues that corruption perpetuates illegitimate power structures, erodes public trust, weakens democratic institutions, and fosters socio-political instability. Strengthening Anti-Corruption Education requires a contextual, practice-oriented approach supported by an integrated integrity ecosystem involving educational institutions, government bodies, and society at large.